2020
DOI: 10.3390/biom10030467
|View full text |Cite
|
Sign up to set email alerts
|

HO-1 Interactors Involved in the Colonization of the Bone Niche: Role of ANXA2 in Prostate Cancer Progression

Abstract: Background: Prostate cancer (PCa) dissemination shows a tendency to develop in the bone, where heme oxygenase 1 (HO-1) plays a critical role in bone remodeling. Previously by LC/ESI-MSMS, we screened for HO-1 interacting proteins and identified annexin 2 (ANXA2). The aim of this study was to analyze the relevance of ANXA2/HO-1 in PCa and bone metastasis. Methods: We assessed ANXA2 levels using a co-culture transwell system of PC3 cells (pre-treated or not with hemin, an HO-1 specific inducer) and the pre-osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Ser phosphorylation of ANXA2 seems to be an essential event of the secretory process [ 23 ], while Tyr24 phosphorylation of ANXA2 (p-ANXA2-Y24) has been related to the localization of ANXA2 to the endocytic membrane system and the nucleus, and is associated with malignant transformation, EMT, tumor invasion, and metastasis [ 23 26 ]. ANXA2 has recently been linked to the metastasis of several types of cancer, such as prostate [ 27 ], colorectal [ 28 ], and breast cancer [ 29 ]. High expression of ANXA2 promotes the development of GC and is negatively correlated with the clinical prognosis [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ser phosphorylation of ANXA2 seems to be an essential event of the secretory process [ 23 ], while Tyr24 phosphorylation of ANXA2 (p-ANXA2-Y24) has been related to the localization of ANXA2 to the endocytic membrane system and the nucleus, and is associated with malignant transformation, EMT, tumor invasion, and metastasis [ 23 26 ]. ANXA2 has recently been linked to the metastasis of several types of cancer, such as prostate [ 27 ], colorectal [ 28 ], and breast cancer [ 29 ]. High expression of ANXA2 promotes the development of GC and is negatively correlated with the clinical prognosis [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding HMOX1 , we previously performed a similar analysis using these three databases, which revealed no significant differences in mRNA expression levels among tumoral and non-tumoral prostate tissue, but demonstrated that PCa patients with higher expression of HMOX1 showed longer RFS (HR: 0.5, p = 0.021) [ 36 ]. Herein, we found that the association between higher HMOX1 levels and longer RFS was not modified by LDHA expression ( Figure 6 D).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have reported that HO-1 modulates bone remodeling and alters the communication between PCa and bone cells [ 35 ]. We have also demonstrated that HO-1 induction affects annexin 2 localization and calcium metabolism in osteoclasts co-cultured with PCa cells, thus suggesting the capability of HO-1 to modify the bone tumor niche [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total cell lysates and immunoblot analysis were carried out as previously described [ 18 ]. Briefly, cells were lysed with RIPA buffer (Tris HCl 50 mM pH 7.4; NaCl 150 mM; ethylenediaminetetraacetic acid (EDTA) 20 mM pH 8; sodium deoxycholate 1%; SDS 0.1%; Triton X-100 1%, 1 mM Na 3 VO 4 , 20 mM NaF, and 1 mM Na 4 P 2 O 7 , pH 7.9) and homogenized.…”
Section: Methodsmentioning
confidence: 99%